2014
DOI: 10.1177/1535370214522177
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide protects against hypoxia/reoxygenation-induced apoptosis by improving mitochondrial function in H9c2 cells

Abstract: Glucagon-like peptide-1 (GLP-1) analogues might exert the cardioprotective effects via attenuating apoptosis. This study aimed to determine the protective effects and mechanism of exenatide, a GLP-1 analogue, on cardiomyocyte apoptosis using an in vitro model of hypoxia/reoxygenation (H/R). H9c2 cells were employed to establish an in vitro model of H/R. 200 nM exenatide pretreatment significantly reduced apoptosis measured by flow cytometry. To further study the antiapoptotic mechanism of exenatide, we used fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…Cardiomyocyte apoptosis induced by I/R is an essential process in the progression of heart failure. Mitochondria play a crucial role in cardiomyocyte apoptosis under hypoxic conditions [3,4]. This study showed that H/R treatment caused mitochondrial dysfunction and cardiomyocyte apoptosis, whereas, pretreatment with geniposide improved mitochondrial dysfunction and attenuated mitochondria-dependent cell apoptosis.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Cardiomyocyte apoptosis induced by I/R is an essential process in the progression of heart failure. Mitochondria play a crucial role in cardiomyocyte apoptosis under hypoxic conditions [3,4]. This study showed that H/R treatment caused mitochondrial dysfunction and cardiomyocyte apoptosis, whereas, pretreatment with geniposide improved mitochondrial dysfunction and attenuated mitochondria-dependent cell apoptosis.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to their significant role in cell apoptosis, mitochondria are also the primary sources of oxidative stress during H/R [3,10]. ROS and RNS are products of mitochondrial oxidative stress, and production of ROS is a vital step in the mitochondria-dependent apoptosis pathway [3,4,27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations